RELEVANSI EPISTEMOLOGI KEPEMIMPINAN JAWA DALAM PENGELOLAAN LEMBAGA PENDIDIKAN MODERN - Risa Sofiati; Syamsul Ma'arif; Ahwan Fanani (STKIP Pesisir Selatan, 2026)
This study aims to analyze the concept of Javanese leadership philosophy from an educational perspective, identify the leadership characteristics of school principals in the modern era, and examine the relevance of Javanese leadership values ​​to current school principal leadership. The research is motivated by the increasingly complex challenges of modern educational leadership that not only demand managerial skills, but also the ability to build humanistic social relationships based on local cultural values. This study uses a qualitative approach with a case study type. Data were collected through semi-structured interviews, participant observation, and documentation involving the principal, vice principal, senior teachers, and education staff selected using purposive sampling and snowball sampling techniques. Data analysis was carried out using the interactive model of Miles, Huberman, and Saldaña through the stages of data reduction, data presentation, and drawing conclusions. The results show that Javanese leadership philosophy is understood as a moral and ethical foundation in the management of modern educational institutions through the values ​​of tepa selira, andhap asor, nguwongke wong, and the concept of Hasta Brata. School principals in the modern era are required to possess adaptive, collaborative, and humanistic characteristics, as well as the ability to integrate managerial skills with social and cultural sensitivity.